Railway Traction System Based on Power Electronic Transformer - Rao, M.Subba; Sobhan, P.V.S.; Ahammad, Shaik Naseer (International Journal of Engineering and Technology, 2018)
In this work design and development of Power Electronics transformer (PET) – based railroad traction system presented. Conventional system is more weight, less efficient and more size. To overcome problems in conventional system PET based system is proposed. The simulation results are carried out by MATLAB/SIMULINK software for, 25kV, 50Hz Supply, which is given to the Locomotive which draws the Power (P) of 400kW.